An open‐label, nonrandomized, phase Ib feasibility study of cusatuzumab in patients with nasopharyngeal carcinoma. Issue 6 (27th October 2021) - De Meulenaere, Astrid; Vermassen, Tijl; Creytens, David; De Keukeleire, Stijn; Delahaye, Tim; Deron, Philippe; Duprez, Fréderic; Fung, Samson; Pauwels, Patrick; Ferdinande, Liesbeth; Rottey, Sylvie
Abstract: CD70 is expressed in up to 80% of nasopharyngeal carcinoma (NPC) cases. Cusatuzumab is a humanized anti‐CD70 monoclonal antibody, with dual action mechanisms: induction of cytotoxicity against CD70 + tumor cells and reduction in CD70‐CD27 signaling mediated immune evasion. The aim of this study was to assess the safety, pharmacokinetic profile, immunogenicity, pharmacodynamic profile, and preliminary activity of cusatuzumab in advanced NPC. Eleven patients were enrolled: one patient was assigned to arm A (adjuvant cusatuzumab monotherapy after curative chemoradiation), nine patients to arm B (cusatuzumab monotherapy; noncurative setting), and one patient to arm C (cusatuzumab + chemotherapy; noncurative setting); irrespective of tumoral CD70 expression. Both patients in arms A and C completed the study. All patients in arm B discontinued at an early stage. Five patients experienced grade greater than or equal to 3 nondrug related treatment‐emergent adverse events, most commonly fatigue and pneumonia (18%). An infusion‐related reaction was observed in two of 11 patients. Laboratory results showed no trend over time. Seven patients were eligible for response evaluation. No objective response to cusatuzumab was observed with stable disease being the best response. The current study indicates that the safety profile of cusatuzumab (with or without concurrent chemotherapy) is manageable in patients with advanced NPC, which is consistent with known safety profile. Limited activity of cusatuzumab in advanced NPC was observed. Combination therapies of cusatuzumab and other types of therapy should be explored for the improvement of activity in NPC and other CD70‐expressing malignancies.